2016
DOI: 10.3920/wmj2015.1906
|View full text |Cite
|
Sign up to set email alerts
|

A mycotoxin-dedicated total diet study in the Netherlands in 2013: Part II – occurrence

Abstract: The occurrence of 59 natural toxins was determined in 88 composite food and drink samples of a mycotoxin-dedicated total diet study performed in the Netherlands in 2013. Composite food samples were prepared by pooling foods from a food category (as consumed, e.g. peeled, cooked, etc.) according to their consumption by population groups in the Netherlands. A multi-targeted method based on QuEChERs extraction, dilute and shoot and analysis by liquid chromatography-tandem mass spectrometry was applied to the 88 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 62 publications
0
28
1
Order By: Relevance
“…Regarding mycotoxin presence, the contents determined here were comparable with previous research performed in total diet studies (TDS). López et al [ 22 ] reported DON and ENB contents in pasta at concentrations of 8.7 and 35 µg/kg, respectively. Yau et al [ 23 ] also detected DON in a range of 29.95–33.11 µg/kg in pasta, while in vegetables, legumes, and meat samples, the amounts were lower than 5.0 µg/kg.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding mycotoxin presence, the contents determined here were comparable with previous research performed in total diet studies (TDS). López et al [ 22 ] reported DON and ENB contents in pasta at concentrations of 8.7 and 35 µg/kg, respectively. Yau et al [ 23 ] also detected DON in a range of 29.95–33.11 µg/kg in pasta, while in vegetables, legumes, and meat samples, the amounts were lower than 5.0 µg/kg.…”
Section: Discussionmentioning
confidence: 99%
“…Different extraction procedures of MON from bread were tested in this study: (a) acetonitrile/water (84:16, v/v), (b) acetonitrile/water with 1% formic acid (84:16, v/v), (c) acetonitrile/water with 1% acetic acid (84:16, v/v), (d) QuEChERS extraction with acetonitrile/water with 1% acetic acid (84:16, v/v) plus clean-up with 4 g of magnesium sulphate and 1 g of sodium acetate (Lopez et al 2016 ), (e) acetonitrile/water (50:50 v/v) and (f) water 100%.…”
Section: Methodsmentioning
confidence: 99%
“…HT-2 is also not commonly found in fruits and its derived products and little information is available in bibliography. López et al [22] detected HT-2 in apple juice composite but at levels below the LOQ.…”
Section: Mycotoxin Contents In Juicesmentioning
confidence: 99%